A Case of Canine Hepatitis with Hepatocellular Attack by Non-Neoplastic Perforin-Laden Lymphocytes - Shimon Furusato; Eriko Kondo; Ikki Mitsui; Yu Tsuyama (Veterinary Sciences)
The etiology of canine chronic hepatitis (CH) is unknown, although an autoimmune background has been suggested in some cases of canine CH. An 11 y old spayed female Norwich Terrier showed a marked elevation of liver enzymes with hyperbilirubinemia, regenerative anemia, and thrombocytopenia. A bacterial culture of the surgically excised liver tissue and bile was negative. The histological features of the liver biopsy resembled those of human autoimmune hepatitis except for a paucity of intralesional plasma cells. It was established through immunohistochemistry that CD3-positive perforin-containing T lymphocytes had actively infiltrated the patient’s liver causing hepatocellular apoptosis, implying an autoimmune attack on hepatocytes. The patient’s general condition improved, with normalization of platelet and serum total bilirubin levels, after immunosuppressive therapy with prednisolone and cyclosporine, whereas liver enzymes did not reach the reference interval. The dog died 11 months after the initiation of immunosuppressive therapy. These pathological findings may be one aspect of autoimmune mediation in canine CH.